Rectal bezoar: a rare cause of intestinal obstruction - Emidio, Fábio Caleça (2023)
Bezoars are conglomerates of undigested contents that accumulate in the gastrointestinal tract. They can have different compositions, such as fibers, seeds, vegetables (phytobezoars), hair (trichobezoars), and medication (pharmacobezoars). Bezoars are typically caused by an impaired grinding mechanism of the stomach or interdigestive migrating motor complex, but the composition of ingested material can also play a role in their formation. Gastric dysmotility, previous gastric surgery, and gastroparesis are some of the risk factors that can increase the likelihood of developing bezoars. While bezoars are usually asymptomatic and found in the stomach, they can sometimes migrate to the small intestine or colon and cause complications such as intestinal obstruction or perforation. Endoscopy is essential for diagnosis and etiology, and treatment depends on the composition, which can include chemical dissolution or surgical intervention. We present a case of an 86-year-old woman, who had a bezoar located in an unusual location (rectum), most likely due to migration. This condition led to symptoms of intermittent intestinal obstruction and rectal bleeding. However, due to anal stenosis, the patient was unable to expel the bezoar. Its removal was not possible through various endoscopic techniques. Therefore, it was removed via fragmentation, using an anoscope and forceps, due to its hard/stone-like consistency. This case highlights the importance of considering bezoars in the differential diagnosis of gastrointestinal bleeding and illustrates the importance of prompt diagnosis and appropriate techniques for the removal of bezoars.